Penerapan metode pembelajaran interaktif melalui game bingo untuk meningkatkan minat belajar siswa kelas 3 MIN 10 Blitar - Pawestri, Iqlima Nia Ayu (Maliki Interdisciplinary Journal, 2025)
Based on the observations I made at MIN 10 Blitar, it is known that the method used for the learning process is still monotonous, namely using the lecture method so that many students are bored and do not participate in the learning process. The purpose of this study is to improve and increase students’ interest in learning in Class 3 RA Kartini through the application of interactive learning methods. This effort is carried out by using bingo game media which is expected to increase student involvement and understanding in the subject of Qur’an Hadith. The application of this interactive method also aims to train teachers’ creativity and innovation in managing Qur’an Hadith learning to make it more interesting, fun, and relevant to students’ needs. In writing this article using the Classroom Action Research Method (PTK) to obtain research results. Based on the results of the study, it can be concluded that the application of interactive learning methods through bingo games can increase students’ interest in learning in the subject of Al-Qur’an Hadith in class 3 RA kartini MIN 10 Blitar.